(untitled) (CIPEEX, 2022)
HUNTINGTON’S DISEASE IS AN INHERITED DISEASE THAT CAUSES PROGRESSIVE DEGENERATION OF NERVE CELLS IN THE BRAIN. DESCRIBED BY THE AMERICAN PHYSICIAN GEORGE HUNTINGTON IN 1872, THE DISORDER HAS BEEN EXTENSIVELY STUDIED IN RECENT DECADES. IT WAS EVEN IN 1993, JUST OVER A HUNDRED YEARS AFTER THE FIRST OFFICIAL CASE OF THE DISEASE, THAT SCIENTISTS DISCOVERED THE GENE THAT CAUSES THE DISEASE - LOCATED ON CHROMOSOME 4. THE CHARACTERISTIC SIGNS AND SYMPTOMS OF HUNTINGTON’S DISEASE ARISE AS A RESULT OF THE PROGRESSIVE LOSS OF CELLS NERVES THAT LIE IN A SPECIFIC PART OF THE BRAIN, THE UNDERLYING GANGLIA. DESPITE SEVERAL STUDIES ON THE SUBJECT, IT IS NOT KNOWN FOR CERTAIN HOW THE RELATIONS PREVIOUSLY PROPOSED ACTUALLY INTERFERE WITH THE DISEASE MANIFESTATION. THUS, THE OBJECTIVE OF THIS STUDY IS TO INVESTIGATE AN ASSOCIATION BETWEEN HUNTINGTON’S DISEASE AND THE VARIOUS MOOD DISORDERS IN THE PRECLINICAL, CLINICAL AND POST-CLINICAL PHASES. TO CARRY OUT THE WORK, WE OPTED FOR AN INTEGRATIVE REVIEW OF LITERATURE THAT INCLUDES 20 ARTICLES SELECTED IN FULL BETWEEN THE YEARS 2006 AND 2018 THAT APPROACH HUNTINGTON’S DISEASE AS THE MAIN THEME. THUS, WE FOUND A DISCRETE BUT CONSISTENT RELATIONSHIP BETWEEN THE DISEASE AND MOOD DISORDERS, WE STILL INVESTIGATED THE CONNECTION OF THIS DISEASE WITH THE ALTERATION OF FAMILY HEALTH, ESPECIALLY MENTAL HEALTH.